2014
DOI: 10.1016/j.celrep.2014.05.030
|View full text |Cite
|
Sign up to set email alerts
|

NUCKS Is a Positive Transcriptional Regulator of Insulin Signaling

Abstract: Although much is known about the molecular players in insulin signaling, there is scant information about transcriptional regulation of its key components. We now find that NUCKS is a transcriptional regulator of the insulin signaling components, including the insulin receptor (IR). Knockdown of NUCKS leads to impaired insulin signaling in endocrine cells. NUCKS knockout mice exhibit decreased insulin signaling and increased body weight/fat mass along with impaired glucose tolerance and reduced insulin sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 32 publications
2
59
1
Order By: Relevance
“…Genotypes of NWT and NKO mice were confirmed as described previously (Supplementary Figure S1)13. Alkaline injury was induced within a confined circular area ~2-mm in diameter in the central corneal region in NWT and NKO mice.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Genotypes of NWT and NKO mice were confirmed as described previously (Supplementary Figure S1)13. Alkaline injury was induced within a confined circular area ~2-mm in diameter in the central corneal region in NWT and NKO mice.…”
Section: Resultsmentioning
confidence: 90%
“…The transgenic mouse lines (NWT and NKO) were gifts from Dr Vinay Tergaonkar (IMCB), the Laboratory of NFκB Signaling, Singapore13. Genotypes of all NWT and NKO mice were confirmed (full-length gel image is presented in Supplementary Figure S1) (primary antibody: anti-NUCKS antibody; Abcam 1:200; corresponding secondary antibody: Cell Signaling, 1:1000).…”
Section: Methodsmentioning
confidence: 99%
“…More than 50 genetic loci associated with type 2 diabetes have been identified, thus explaining a modest fraction of heritability [16]. Environmental factors are also crucial for the development of this pathology, and type 2 diabetes and insulin resistance have been directly related to obesity and a sedentary lifestyle [10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…NUCKS1 protein is identi ed as one of the cell cycle-related proteins and participates in the response of DNA damage induction [8,15]. Previous studies had reported that NUCKS1 played a crucial role in the regulation of glucose homoeostasis and insulin signalling [16,17]. Besides, NUCKS1 had been shown to be a key transcriptional regulator and chromatin modi er and it could be a potential bio-marker for human diseases, including cancers and metabolic diseases [18].…”
Section: Discussionmentioning
confidence: 99%